The Influence of Organizational Communication in Supporting an Effective Work Climate in The Starpactions Section of PT Sunstar Engineering Indonesia - Novia, Reni; Junarti, Junarti; Syahshiyah, Nur Hafni; Fajriani, Fajriani; Anjani, Firda (Universitas Negeri Surabaya, 2024)
This study aims to determine the influence of organizational communication on the effective work climate in the Starpaction section of PT Sunstar Engineering Indonesia by formulating a problem on how much influence organizational communication has in supporting an effective work climate in the Starpactions section of PT Sunstar Engineering Indonesia. The limitation in this study is on the working climate in the startpaction section only, not in the whole section. The data collection method uses questionnaire distribution. The population in this study is employees of the Starpaction section, permanent employees, and fixed-time employees of the work agreement. The sampling technique used was a total sampling with a sample of 30 respondents. The data analysis methods used are validity test, reliability test, normality test, linearity test, simple linear regression analysis, and partial significance test (T-test), and Determination Coefficient Test (R-test) using the SPSS 26 application of 2024. The results of the t-test obtained a t-count value of 10,244 while the t-table was 1,701, thus, it can be concluded that t-count > t-table (10,244 > 1,701) From the results of the t-test, a significant value of 0.000 < 0.05 was also obtained so that it can be concluded that organizational communication has a positive and significant effect on the effective work climate in the Starpaction section of PT Sunstar Engineering Indonesia